Potential agricultural and environmental benefits of mulches - a review - Iqbal, Rashid (2021)
This review paper focuses on multiple significant impacts of mulches for the production and establishment of different crops in nature. Mulches conserve the soil moisture, enhance the nutrients status of soil, control the erosion losses, suppress the weeds in crop plants, and remove the residual effects of pesticides, fertilizers, and heavy metals. Mulches improve the aesthetic value of landscapes and economic value of crops. This paper also describes some problems associated with various mulch materials. There are contradictions about mulching materials as some researchers favor mulches and others have denoted some concerns. The selection of mulching material is important with respect to crop type, management practices, and climatic conditions. The appropriate mulching technique could provide the aforementioned benefits to the agro-ecological systems. Therefore, the impacts of low-cost, eco-friendly, and biodegradable mulching materials on soil microbes, nutrient balance, plant growth, and soil erosion should be explored in the future.